Crystal structure of the Mre11–Rad50–ATPγS complex: understanding the interplay between Mre11 and Rad50 - Lim, Hye Seong (Cold Spring Harbor Laboratory Press, 2011)
Communication between Mre11 and Rad50 in the MR complex is critical for the sensing, damage signaling, and repair of DNA double-strand breaks. To understand the basis for interregulation between Mre11 and Rad50, we determined the crystal structure of the Mre11–Rad50–ATPγS complex. Mre11 brings the two Rad50 molecules into close proximity and promotes ATPase activity by (1) holding the coiled-coil arm of Rad50 through its C-terminal domain, (2) stabilizing the signature motif and P loop of Rad50 via its capping domain, and (3) forming a dimer through the nuclease domain. ATP-bound Rad50 negatively regulates the nuclease activity of Mre11 by blocking the active site of Mre11. Hydrolysis of ATP disengages Rad50 molecules, and, concomitantly, the flexible linker that connects the C-terminal domain and the capping domain of Mre11 undergoes substantial conformational change to relocate Rad50 and unmask the active site of Mre11. Our structural and biochemical data provide insights into understanding the interplay between Mre11 and Rad50 to facilitate efficient DNA damage repair.